Platelet hyperactivation in maintained growth hormone-deficient childhood patients after therapy withdrawal as a putative earlier marker of increased cardiovascular risk - Reis, Flávio (2005)
GH deficiency (GHD) is associated with a higher risk of vascular disease, whose pathophysiological mechanisms remains not yet fully elucidated. This study aimed to assess the main cardiovascular risk indexes, plasma catecholamines content, and the platelet function in childhood-onset GHD patients. Some of the main clinical examinations related with cardiovascular risk, plasma catecholamines content, as well as platelet intracellular free calcium concentration ([Ca(2+)](i)), whole-blood aggregation, and morphology were evaluated in childhood-onset GHD patients treated with GH for a variable period and off GH therapy for at least 2 yr before entry into study and in sex-, age-, and body mass index-matched control groups. Among the patients, group 1 (GHD-1) has recovered GH levels after withdrawal, whereas group 2 (GHD-2) has remained GH deficient. Minor differences on the cardiovascular risk indexes were observed between the groups. Plasma catecholamine concentrations in the GHD groups did not statistically differ from the control group, but higher adrenaline content was observed in the GHD-2 group when compared with the GHD-1 one. Basal and thrombin-evoked [Ca(2+)](i) and platelet aggregation were identical between the GHD-1 group and the matched control. However, the GHD-2 group has increased thrombin-evoked [Ca(2+)](i) (297.0 +/- 15.7 Deltanmol/liter; P < 0.01), collagen, and ADP-induced platelet aggregation (33.3 +/- 4.3 and 12.5 +/- 2.1 Omega, respectively; P < 0.05) vs. the control-2 group (Delta[Ca(2+)](i): 102.1 +/- 13.6 Deltanmol/liter; aggregation: 19.6 +/- 2.9 and 6.2 +/- 0.8 Omega). The platelet hyperreactivity state in the GHD-2 was reinforced by morphologic studies of electron microscopy. In conclusion, there were minor differences between the GHD-1 group and the controls, which might be due to the recovery of GH levels after therapy withdrawal. However, the maintained GHD group, despite minor cardiovascular risk index differences, has increased [Ca(2+)](i) and aggregation, which could indicate a hyperactivation state that might be viewed as an earlier marker of cardiovascular disturbances